2020
DOI: 10.3390/brainsci10010036
|View full text |Cite
|
Sign up to set email alerts
|

How the Brain Understands Spoken and Sung Sentences

Abstract: The present study investigates whether meaning is similarly extracted from spoken and sung sentences. For this purpose, subjects listened to semantically correct and incorrect sentences while performing a correctness judgement task. In order to examine underlying neural mechanisms, a multi-methodological approach was chosen combining two neuroscientific methods with behavioral data. In particular, fast dynamic changes reflected in the semantically associated N400 component of the electroencephalography (EEG) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, they did equally well in infant-directed speech. Similarly, Rossi et al [14] found no differences between speech and songs in a combined EEG-NIRS study on semantic processing in healthy adults. Taken together, these data suggest that the presentation of verbal material as song may not be sufficient to enhance vocabulary learning or language comprehension in healthy individuals (but see [40]).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…However, they did equally well in infant-directed speech. Similarly, Rossi et al [14] found no differences between speech and songs in a combined EEG-NIRS study on semantic processing in healthy adults. Taken together, these data suggest that the presentation of verbal material as song may not be sufficient to enhance vocabulary learning or language comprehension in healthy individuals (but see [40]).…”
mentioning
confidence: 94%
“…If rhythmic processing disabilities are indeed the basis of speech and language disorders, then useful avenues for prevention and intervention could lie in (i) increasing the regularity of stimuli, or (ii) strengthening individual rhythmic abilities with the aim at improving neuronal entrainment [37][38][39]. Several studies in this Special Issue deal directly or indirectly with these ideas, either by exploring processing benefits of rhythmically highly regular stimuli such as songs [13,14] or poems [10,11], or by discussing potential protective or curative effects of music-based rhythm training on language skills [7,8,10,12,15,16]. Even though the results are promising, they also raise a number of questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A further strand of research has focused on the common auditory processing of temporal regularities (Boll-Avetisyan et al, 2020;Fotidzia et al, 2018;Lagrois et al, 2019;Reybrouck and Podlipniak, 2019). These are thought to promote higher-level linguistic functions (Breen et al, 2019;Frey et al, 2019;Fotidzis et al, 2018: Richards andGoswami, 2019;Rossi et al, 2020;Snijders et al, 2020), possibly through neuronal entrainment (Myers et al, 2019). For instance, Lagrois and colleagues (2019) found that so-called 'beat deaf individuals', those who have beat-finding deficits in music, showed deficits in synchronising tapping with speech rhythm, and more generally, in regular tapping without external rhythms.…”
Section: Explanations Of the Relationships Between Music And Languagementioning
confidence: 99%
“…A further strand of research has focused on the common auditory processing of temporal regularities (Boll-Avetisyan et al, 2020;Fotidzia et al, 2018;Lagrois et al, 2019;Reybrouck & Podlipniak, 2019). These are thought to promote higher level linguistic functions (Breen et al, 2019;Frey et al, 2019;Fotidzis, et al, 2018: Richards andGoswami, 2019;Rossi et al, 2020;Snijders,et al, 2020) possibly through neuronal entrainment (Myers et al, 2019). For instance, Lagrois and colleagues (2019) found that so called beat deaf individuals, those who have beat finding deficits in music, showed deficits in synchronizing tapping with speech rhythm, and more generally, in regular tapping without external rhythms.…”
Section: Explanations Of the Relationships Between Music And Languagementioning
confidence: 99%